2021
DOI: 10.3389/fspas.2021.755100
|View full text |Cite
|
Sign up to set email alerts
|

Planetary Mass Spectrometry for Agnostic Life Detection in the Solar System

Abstract: For the past fifty years of space exploration, mass spectrometry has provided unique chemical and physical insights on the characteristics of other planetary bodies in the Solar System. A variety of mass spectrometer types, including magnetic sector, quadrupole, time-of-flight, and ion trap, have and will continue to deepen our understanding of the formation and evolution of exploration targets like the surfaces and atmospheres of planets and their moons. An important impetus for the continuing exploration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 219 publications
(261 reference statements)
0
13
0
Order By: Relevance
“…In addition to existing instruments, the development of new instruments or instrument capabilities to detect chirality in spaceflight is a necessary component in the search for signs of past life. Advancements in the fields of organic separation (e.g., [500][501][502][503][504]) and detection through mass spectrometry [505,506] are needed to enhance the field of chiral separation on spaceflight missions. Refinement of traditional chiral separation and detection methods as well as the development of new analytical strategies to investigate chiral organics [407,420,[507][508][509] and minerals [510] should be prioritized.…”
Section: Next Generation Instrumentationmentioning
confidence: 99%
“…In addition to existing instruments, the development of new instruments or instrument capabilities to detect chirality in spaceflight is a necessary component in the search for signs of past life. Advancements in the fields of organic separation (e.g., [500][501][502][503][504]) and detection through mass spectrometry [505,506] are needed to enhance the field of chiral separation on spaceflight missions. Refinement of traditional chiral separation and detection methods as well as the development of new analytical strategies to investigate chiral organics [407,420,[507][508][509] and minerals [510] should be prioritized.…”
Section: Next Generation Instrumentationmentioning
confidence: 99%
“…The development for space applications over the last few decades has focused on minimizing power and mass while improving the mass resolution (m/Δm, Δm being at full width at half maximum, FWHM) of these instruments. These developments with emphasis on space applications have been extensively reviewed and covered by others (Palmer and Limero, 2001;Johnson et al, 2012;Snyder et al, 2016;Ren et al, 2018;Arevalo et al, 2020;Chou et al, 2021). The mass analyzer and the detector (often referred to as the back-end) function relatively independently of the front-end, which may involve a GC or a laser desorption and ionization (LDI) instrument.…”
Section: Mass Spectroscopymentioning
confidence: 99%
“…The development of miniaturized mass spectrometers has experienced a surge over the last decade, and we refer the interested reader to a few excellent general review papers (Snyder et al, 2016;Mielczarek et al, 2020) and a few related to planetary exploration applications (Arevalo et al, 2020;Chou et al, 2021). A few ongoing developments are worth highlighting here, such as the quadrupole ion trap (QIT) MS onboard ISS (Darrach et al, 2015;Madzunkov et al, 2016;Schowalter et al, 2019), the linear ion trap (LIT) MS onboard the Rosalind Franklin rover (Arevalo et al, 2015;Goesmann et al, 2017), the multi-bounce time-of-flight MS developed for the Europa Clipper mission (Brockwell et al, 2016), and the adaption and miniaturization of the Orbitrap (Arevalo et al, 2018).…”
Section: Mass Analyzersmentioning
confidence: 99%
“…A so-called agnostic biosignature, such as a generalizable measure of complexity, considers the possibility that alien life may be distinct from life as we know it on Earth. Determining the signatures of life is challenging because we have no universal definition of life, we only have the example of life as we find it on Earth (Barge et al 2022;Bartlett & Wong 2020;Chou et al 2021aChou et al , 2021bCleland 2019aCleland , 2019bGuttenberg et al 2021;Johnson et al 2018;Marshall et al 2021). However, recent work has demonstrated that general measures of molecular complexity exhibit strong associations with "biogenicity" and hence could be used as agnostic chemical biosignatures (Cleaves et al 2023;Guttenberg et al 2021;Marshall et al 2021).…”
Section: Introductionmentioning
confidence: 99%